Epistemologi Ilmu dalam al-Qur’an Berdasarkan Tafsir Klasik dan Modern - Yogi Juliansyah (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
The development of science today is often detached from divine values, thus giving rise to a moral and spiritual crisis. This study departs from the need to re-understand the meaning of science in the Qur'an in order to harmonize intellectual and spiritual progress. The purpose of this study is to understand the concept of science and its various types in the Qur'an as depicted in QS. Al-'Alaq [96]: 1-5, QS. Al-Baqarah [2]: 31-32, and QS. An-Nahl [16]: 78. This study uses a qualitative-descriptive method based on literature studies, through the tafsīr maudhū‘ī (thematic) approach, by tracing the explanation of M. Quraish Shihab in Wawasan Al-Qur'an. The results of the study show that the Qur'an places science as the basis of human nobility, which includes rational, spiritual, and moral dimensions. The three verses examined illustrate that knowledge originates from God, serves to elevate human dignity, and develops through the five senses, reason, and heart. This article contributes to enriching understanding of Islamic epistemology by emphasizing the importance of a divine orientation in the development of knowledge.